The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.21608/ajesa.2015.164015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Conventional Farming on the Activity of Spider Assemblage (Araneae) in Some Medicinal Plants in Fayoum-Egypt

Abstract: Spider activity occurred on three medicinal plants (Wormwood, Chrysanthemum and Spearmint) with organic and inorganic fertility was assessed using pitfall traps in Fayoum, Egypt. Community composition of the organic and the conventional cultivation of collected spiders were determined throughout the period of study using the Shannon-Wiener and Simpson Indices of diversity. Totals of 387 and 350 individuals including 20 and 24 species in the organic and the conventional cultivation, respectively, were of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…considered "eudominant", W. fidelis was "dominant". Similar result was obtained by (Rizk et al, 2015) who found that W. fideles, and Pardosa spp. ranged between "eudominant" and "dominant" according to Weigmann classification of dominance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…considered "eudominant", W. fidelis was "dominant". Similar result was obtained by (Rizk et al, 2015) who found that W. fideles, and Pardosa spp. ranged between "eudominant" and "dominant" according to Weigmann classification of dominance.…”
Section: Discussionsupporting
confidence: 89%
“…This result coincide with (Bengtsson et al, 2005;and Schmidt et al, 2005) who indicated that organic farming increases species richness and densities. Lycosidae was most abundant family, (Feber et al, 1998;Tahir and Butt, 2009;and Rizk et al, 2015) were reported that Lycosidae was the most abundant family. Lycosidae was considered "constant" (66.19 and 60.08%) in chia and (50.23 and 57.77%) in quinoa for conventional and organic cultivation respectively.…”
Section: Discussionmentioning
confidence: 98%